2004
DOI: 10.1002/ijc.20710
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk in relation to different types of hormone replacement therapy in the E3N‐EPIC cohort

Abstract: Most epidemiological studies have shown an increase in breast cancer risk related to hormone replacement therapy (HRT) use. A recent large cohort study showed effects of similar magnitude for different types of progestogens and for different routes of administration of estrogens evaluated. Further investigation of these issues is of importance. We assessed the risk of breast cancer associated with HRT use in 54,548 postmenopausal women who had never taken any HRT 1 year before entering the E3N-EPIC cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
194
2
33

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(238 citation statements)
references
References 42 publications
9
194
2
33
Order By: Relevance
“…Studies on HRT have shown that a combination of oestrogen plus progestin increases breast cancer risk more than oestrogen alone (Chlebowski et al, 2003;Fournier et al, 2005;Stefanick et al, 2006), but these involve administration to postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on HRT have shown that a combination of oestrogen plus progestin increases breast cancer risk more than oestrogen alone (Chlebowski et al, 2003;Fournier et al, 2005;Stefanick et al, 2006), but these involve administration to postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Randomised trials and observational studies have strongly suggested that some synthetic progestagens, when added to an oestrogen in HRT, increase breast cancer risk more than the use of oestrogen alone (Chlebowski et al, 2003;Fournier et al, 2005;Stefanick et al, 2006). However, data on the impact of the premenopausal use of progestagens on breast cancer risk are limited.…”
mentioning
confidence: 99%
“…Total 825 -récemment, les résultats finaux du bras oestrogènes seuls (ECE) de l'étude WHI [17] ont révélé de nouvelles contradictions : il n'a été observé aucune augmentation du risque de cancer du sein dans le groupe ECE comparativement au placebo, voire une tendance non significative à la baisse du nombre de cancers du sein, dans le groupe traité ; -enfin, la très récente publication de Fournier et al [8], sur la cohorte E3N a principalement montré :…”
Section: Sud-est 35unclassified
“…Nous nous sommes centrés sur les THS « à la française » i.e. ceux les plus prescrits en France et non étudiés par la WHI [2] et la MWS [3], ou non distingués par leurs propriétés pharmacologiques, en ce qui concerne les progestatifs, dans le cadre de l'étude E3N [8].…”
Section: Sud-est 35unclassified
See 1 more Smart Citation